From Modern Production to Imagined Primitive : The Social World of Coffee from Papua New Guinea - West, Paige, 1969- (Book collections on Project MUSE., 2012)
West looks at the process from which coffee is grown, gathered, sorted, shipped, and served from the highlands of Papua New Guinea to coffee shops in far away places. She shows how coffee becomes a commodity, the different forms of labor involved, and the way that coffee shapes the lives and understandings of those who grow, process, export, sell and consume coffee.